2004
DOI: 10.2337/diabetes.53.7.1831
|View full text |Cite
|
Sign up to set email alerts
|

Tumstatin Peptide, an Inhibitor of Angiogenesis, Prevents Glomerular Hypertrophy in the Early Stage of Diabetic Nephropathy

Abstract: In the early stage of diabetic nephropathy (one of the major microvascular complications of diabetes) glomerular hyperfiltration and hypertrophy are observed. It is clinically important to regulate glomerular hypertrophy for preventing glomerulosclerosis. The number of glomerular endothelial cells is known to be increased in diabetic nephropathy associated with enlarged glomerular tufts, suggesting that the mechanism is similar to that of angiogenesis. Tumstatin peptide is an angiogenesis inhibitor derived fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
138
2
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(165 citation statements)
references
References 47 publications
22
138
2
3
Order By: Relevance
“…Glomerular morphometric analysis demonstrates that diabetic C57BL/6, 129Sv, and CD1 mice develop glomerular hypertrophy, confirming previous studies (19,20) (Fig. 1C).…”
Section: Resultssupporting
confidence: 74%
“…Glomerular morphometric analysis demonstrates that diabetic C57BL/6, 129Sv, and CD1 mice develop glomerular hypertrophy, confirming previous studies (19,20) (Fig. 1C).…”
Section: Resultssupporting
confidence: 74%
“…in the STZ-diabetic rat [26][27][28][29][30]. In these studies the most pronounced upregulation was observed in the early stages of the disease.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, neonatal HP diet has been demonstrated to accelerate postnatal weight gain with mesenteric fat mass accretion, hypertriglyceridemia, hyperinsulinism, and resistance to leptin (20,27). These changes are known to increase SNGFR, to affect the glomerular endothelium barrier, to impair endothelium-dependent vasodilatation, and to stimulate the sympathetic nervous activity responsible for HT, one of the leading causes of CKD (28)(29)(30)(31)(32). Even though blood pressure was not monitored in the current study, we hypothesize that such metabolic, hormonal, and vascular changes enhanced the adaptive glomerular hemodynamic changes and renal injury already acquired during the neonatal period and accelerated the occurrence of proteinuria and glomerular sclerosis (33).…”
Section: Discussionmentioning
confidence: 99%